NON-LIVING CREATURE PERSONIFICATION IN WIZ KHALIFA SELECTED SONGS - antari, budi (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2023)
songs as one of literary works often used figurative languange, such as personification. To gives a human attribute to things, animal or abtract object. The theory used is the theory of (Zhu, 1991) about Non-living personification and describe the meaning of the lyrics using the theory of meaning from (Leech, 1981)., The method used in this study is qualitative research, where the data is collected by observation and note taking methods. After analyzing the data, the writer concludes that in each of the selected songs, namely: Sucker of pain, Speed ​​me up, Medicated, Hope less romantic, there are some lyrics that contain Non Living personification based on personification theory by (Zhu, 1991), The result shows there 5 data for non-living personification in the lyrics. The sentences that contained this personification have conceptual, connotative, social and thematic meaning based on the theory of meaning by (Leech, 1981).